A deep learning approach for prediction of ADHD using brain structure - Siam, Shafin Ahad; Datta, Durjoy; Hossain, S.M.Kawsar; Nobel, MD.Nishat Ahmed; Ahamed, Ashik (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.